Genetic diversity of local sorghum (Sorghum bicolor) genotypes of East Java, Indonesia for agro-morphological and physiological traits - Sulistyawati Sulistyawati; DYAH ROESWITAWATI; JABAL TARIK IBRAHIM; MAFTUCHAH (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Sulistyawati, Roeswitawati D, Ibrahim JT, Maftuchah. 2019. Genetic diversity of local sorghum (Sorghum bicolor) genotypes of East Java, Indonesia for agro-morphological and physiological traits. Biodiversitas 20: 2503-2510. Sorghum (Sorghum bicolor (L.) Moench) has great potential to be cultivated because it has extensive adaptability, tolerant to drought and puddles, can produce on marginal land and relatively resistant to pests and diseases. To meet the food requirement, sorghum can be grown in Indonesia as an alternative food source other than rice. This study aims to obtain information on the agro-morphological and physiological characters of nine local sorghum genotypes in East Java, Indonesia so that they can be used as parents in improving the nature of varieties. The experiment was conducted in a Randomized Block Design, using nine local sorghum genotypes from East Java in three replications. The nine local sorghum genotypes are Sb.Pas, Sb.Lmg 1, Sb.Lmg 2, Sb.Tbn, Sb.Spg 1, Sb.Spg 2, Sb.Tag 1, Sb.Tag 2 and Sb.Jbg. The result showed that nine genotypes that are characterized have a variety of morphological (quantitative and qualitative), agronomic and physiological characters. According to the whole characters observed, there are five genotypes that are recommended for breeding programs, namely Sb.Lmg 1, Sb.Tbn, Sb.Spg 2, Sb.Tag1 and sb.Tag2. This can be proved by the morphological character, genotype Sb.Lmg 1, Sb.Tbn, Sb.Spg 2, Sb.Tag 1 and Sb.Tag2 have a high value of Agronomy character, genotype Sb.Tbn, Sb.Tag 1 and Sb.Tag 2 noted highest production acres-1 harvest age of genjah and medium; the Physiology character, high protein and carbohydrate substances reached by the Sb.Lmg 1 genotype, Sb.Tbn and Sb.Spg 2.